2002
DOI: 10.1074/jbc.m200528200
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of Stargazin by Protein Kinase A Regulates Its Interaction with PSD-95

Abstract: Stargazin is a transmembrane protein that interacts with AMPARs 1 and regulates their synaptic targeting (1, 2). The stargazer, a spontaneous mutant mouse (3) with defects in the stargazin gene (Cacng2) (4), displays an absence seizure (also known as petit-mal or spike-wave) and, as the name implies, a head-tossing movement, probably because of a defect in the vestibular system (3). In addition, stargazer mice develop an ataxic gait (3) and severe impairment in classical eye-blink conditioning (5), probably be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
98
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 34 publications
4
98
0
Order By: Relevance
“…1G-I), confirming that this major synaptic protein of the excitatory post-synaptic density was appropriately sorted to the plasma membrane of cortical pyramidal neurons in culture. Furthermore, PSD-95 is known to associate directly with NMDA ionotropic glutamate receptors (NMDA-R) and indirectly with AMPA ionotropic glutamate receptors (AMPA-R) via stargazin (Kornau et al, 1995;Chen et al, 2000;El-Husseini et al, 2000;Chetkovich et al, 2002;Choi et al, 2002;Schnell et al, 2002), and has been shown to directly interact with the 5-HT 2A receptor (Xia et al, 2003). As expected, PSD-95 in cultured neurons co-localized with NMDA receptors (data not shown) and 5-HT 2A receptors (Fig.…”
Section: Resultssupporting
confidence: 64%
“…1G-I), confirming that this major synaptic protein of the excitatory post-synaptic density was appropriately sorted to the plasma membrane of cortical pyramidal neurons in culture. Furthermore, PSD-95 is known to associate directly with NMDA ionotropic glutamate receptors (NMDA-R) and indirectly with AMPA ionotropic glutamate receptors (AMPA-R) via stargazin (Kornau et al, 1995;Chen et al, 2000;El-Husseini et al, 2000;Chetkovich et al, 2002;Choi et al, 2002;Schnell et al, 2002), and has been shown to directly interact with the 5-HT 2A receptor (Xia et al, 2003). As expected, PSD-95 in cultured neurons co-localized with NMDA receptors (data not shown) and 5-HT 2A receptors (Fig.…”
Section: Resultssupporting
confidence: 64%
“…Specific ␤PIX antibodies were affinity-purified after immobilizing the protein to a polyvinylidene difluoride membrane. The following antibodies have been described: EGFP (1167) (35), PSD-95 (SM55) (35), Shank (3856, pan-Shank) (10), Shank (1123, pan-Shank) (9), and GIT1 (du139) (36). The following antibodies were obtained from commercial sources: HA rabbit polyclonal (Santa Cruz Biotechnology), FLAG M2 monoclonal (Sigma), synaptophysin SVP38 (Sigma), MAP2 (Sigma), phospho-neurofilament H N52 (Sigma), PAK N-20 (Santa Cruz Biotechnology), vinculin hVIN-1 (Sigma), and p130Cas (Transduction Laboratories).…”
Section: Methodsmentioning
confidence: 99%
“…For example, PKA phosphorylation of a threonine residue (T321) in the -TTPV motif of ␥2 disrupts binding by PSD-95 (Chetkovich et al, 2002;Choi et al, 2002). Thus, phosphorylation by PKA or other kinases is a reasonable candidate for regulating the synaptic targeting of ␥2 and associated AMPARs by other PDZ proteins in vivo, including MAGI-2.…”
Section: Regional Specificity Of Tarp-magi-2 Interactions In Brainmentioning
confidence: 99%